Draft Seventh Five Year Plan 1985-90 and Annual Plan 1985-86 Government of Assam - Planning Commission (Planning Commission, 1985)
Agriculture is the mainstay of the economy of Assam, and as such Agricultural development was given priority in the at Five Year plans of Assam. The size of the State, sixth Five year Plan was Rs. 1115.00 crores out of which the approved outlay for agriculture proper was Rs. 61.00 crores. The impact of planned agricultural development in the State, during the Sixth plan, period is not as dismal. as it appears, to be from the production Statistics which do not take into account the loss, of production, due to natural calamities, like flood and drought.
Government of Assam